Avirulent strain of Colletotrichum induces a systemic resistance in strawberry - Salazar, Sergio Miguel; Grellet Bournonville, Carlos Froilan; Chalfoun, Nadia Regina; Castagnaro, Atilio Pedro; Diaz Ricci, Juan Carlos (Springer, 2019)
Strawberry plants exposed to an avirulent isolate of Colletotrichum fragariae acquired strong resistance against a virulent strain of C. acutatum. Biochemical, morphological and molecular markers indicated that the strong defence response was associated with an oxidative burst and a transient accumulation of salicylic acid (SA). A maximum accumulation of H2O2 and O2 − was observed 8 h after inoculation (hai), callose was detected 48 hai, and a peak of SA was observed 48 hai. Biochemical and phytopathogenic analyses carried out in non-treated tissues revealed that the defence response was systemic and remained fully active 60 days after the first inoculation. Experiments also showed that the resistance acquired by mother plants after the inoculation with the avirulent isolate could be passed to daughter plants through runners. Further characterization of the induced systemic resistance showed that the resistance was not only effective against a virulent strain of C. acutatum but also against Botrytis cinerea.